The Competitive Older Athlete: A Review of Psychosocial and Sociological Issues. Issue 1 (January 2016) - Dionigi, Rylee A.
Abstract : This review focuses on works that examine the participation of older people in sport from a critical social science perspective. It reveals how, on the one hand, sport can provide many benefits for participants, but on the other hand it also creates psychosocial and sociocultural issues for older participants that need to be managed by society, individuals working with older people and older people themselves. The author argues that while sport should be made available to older people, participation in sport should not be an expectation for all as we age because of access, equity and personal issues.